Badminton smashing punch training method junior high school athletes eternal badminton association - Endrawan, I Bagus; Sukmawati, Noviria; Fikri, Aprizal; Wardana, Mitra (Physical Education Departement of University PGRI Jombang, 2024)
Badminton is a sport that requires a high level of technical and strategic expertise. Correct positioning allows the player to have an optimal viewing angle of the game and makes it easy to respond to the movement of the shuttlecock. The purpose of this study was to evaluate the application of smash precision training methods on junior badminton players in the Eternal Badminton Union. This study adopts a quantitative approach by using experimental methods pretest-post-test design of one group. This experiment will be conducted for six weeks with a training frequency of four sessions per week. The population and subjects were junior athletes of the Eternal Badminton Union, which numbered 15 people, namely nine male athletes and six female athletes. The data analysis using SPSS statistical software 20. The research instrument used questionnaires, smash accuracy tests before and after training, and field observations to evaluate the effectiveness of smash precision training methods in junior badminton athletes. The results showed that the drill method can improve the accuracy of badminton strokes of junior athletes from the Badminton Association of PB Abadi. Further research can develop different training methods by combining different training methods. This will help to better identify the factors that can improve the smash badminton results of junior athletes.